(untitled) (Medical Forum Monthly, 2024)
Objective: To study the prevalence of peripheral neuropathy and evaluate the clinical nerve dysfunction in patients with chronic kidney disease. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Medical ward Nishtar hospital, Multan from May 2018 to May 2019. Materials and Methods: Eighty patients of clinically and biochemically proven chronic kidney disease were selected for study. Non probability consecutive sampling was used. Patients were assessed or both sensory and motor nerve dysfunction. SPSS software was used for data analysis. Main variables of study were creatinine clearance and neuropathy of peripheral nerves. Results: Affected patients percentage with reference to overt and subclinical neuropathy was noted as 67.5%. Overt neuropathy and subclinical neuropathy observed as 35.2% and 64.8%, respectively. Patients affected with percentage with reference to the type of peripheral neuropathy were noted 67.5%. Sensory-motor, sensory and motor was observed as 31.5%, 14.8% and 53.7%, respectively. Conclusion: Peripheral neuropathy is highly associated with chronic kidney disease and severity and prevalence of neuropathy increases with worsening in renal failure. Early diagnosis and strict compliance required to overcome this condition.